The Role of The Personal in Mediating Entrepreneurship Education Towards Entrepreneurial Interests - Ahmad Firman (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2022)
This study aims to analyze (1) to find out and explain the influence of Entrepreneurship Education on the Personality of Management Students, (2) to find out and explain the existence of personal influence on entrepreneurial interest, (3) to determine and explain the influence of Entrepreneurship Education on Entrepreneurial Interests of Management S1 Students, (4) To find out and explain the influence of Personal roles in mediating Entrepreneurship Education on Entrepreneurial Interests of S1 Management Students. This research belongs to the type of research in the category of explanatory research, which is to explain a relationship between variables through hypothesis testing. The research sample amounted to 125 people. The sample in this study using the census method, from the total population will be sampled in this study. The data analysis method is part of the analysis process with methods that are appropriate to the type of research after the research data collection stage. In order to analyze the data the author uses the statistical technique Partial Least Square (PLS). The results of the research from the results of data analysis using the statistical partial least square (PLS) technique which can be seen from the results of data analysis which states that Entrepreneurship Education has a positive and significant influence on Personal, Personal can have a positive and significant influence on Entrepreneurship Interest. positive and significant influence on Entrepreneurial Interest and Entrepreneurship Education indirectly (through the Personality variable) significantly influence the Entrepreneurial Interest of S1 Management Students at ITB Nobel.